The relationship between peer servant leadership, social identity, and team cohesion in intercollegiate athletics. (July 2020) - Worley, Justin T.; Harenberg, Sebastian; Vosloo, Justine
Abstract: Servant leadership is characterized by a leader's emphasis on serving their followers first. Within the sport context, servant leadership has been studied primarily in coaches and has been associated with positive athlete outcomes, such as increased athlete satisfaction, motivation, and performance. However, the impact of servant leadership from an athlete perspective (e.g., formal team captains) has been underexplored. As such, the purpose of the present study was to examine the relationships between peer servant leadership, cohesion, and social identity within intercollegiate athletes. Two hundred and eighty-eight Division I and Division III NCAA intercollegiate athletes participated in the present study (female n = 165; male n = 123; M age = 19.41, SD age = 1.09) and completed the Revised Servant Leadership Profile for Sport (RSLP-S; Hammermeister et al., 2008), Group Environment Questionnaire (GEQ; Carron et al., 1985; Eys et al., 2007), and Social Identity Questionnaire for Sport (SIQS; Bruner & Benson, 2018). Structural equation modeling was used to assess the relationships between peer servant leadership, cohesion, and social identity. Results revealed that peer servant leadership positively predicted cohesion, and this relationship was fully mediated by social identity. The current study supports the effectiveness of peer servant leadership in sport contexts and provides theoretical support for the social identity approach to leadership. Highlights: There is a lack of investigation of servant leadership from a peer perspective in sport. Peer servant leadership positively predicts perceptions of cohesion. Social identity mediates the relationship between peer servant leadership and cohesion. We provide practical implications for athletes, coaches, and sport psychology practitioners.